(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
As a result of intense and ever-growing technological development, as well as the increase of digital media usage in everyday life, communication strategies have undergone profound transformations in order to adapt to specific conditions of online environment. Due to the interactive essence of Internet communication, which is being realized on social media and other online platforms, the need for engaging social media users in creating communication strategies has emerged. Furthermore, demographic trends have resulted in the shift of target audience structure, since generation Y members (i.e. millennials) have growing importance within the structure of contemporary society. This generational cohort, among its other characteristics, can be depicted by its distinct sophistication in terms of communication preferences. To be more precise, this generation expects to be provided with interactive, real-time and personalized communication, which is adjusted to social media platforms they use and can be consumed on the go. Therefore, the aim of this paper is to observe and accentuate the changes in media communication strategies caused by millennials and their extensive use of technology. The results obtained from the research conducted in this paper can be useful for both communication researchers and practitioners, and can be used as guidelines for creating digital communication strategies for millennials.